The Contribution of Concentration and Self-Confidence to Upper Serve Accuracy in Male Volleyball Players - Novilasari, Reni; Budiman, Ali; Sulistiadinata, Heru (Journal of Physical and Outdoor Education, 2025)
This study aims to determine the contribution of concentration and self confidence to the accuracy of upper serve among male volleyball players at the Patriot Club in Cimahi. The research used a correlational method with a quantitative approach. The population in this study consisted of all male volleyball players at the Patriot Club Cimahi, totaling 50 athletes, with a sample of 20 players selected using purposive sampling. The instruments used included the Grid Concentration Test to measure concentration, a questionnaire to assess self confidence, and the AAHPER Serving Accuracy Test to evaluate upper serve accuracy. The results of data analysis showed a significant relationship between concentration and upper serve accuracy, as well as a significant relationship between self-confidence and upper serve accuracy. Furthermore, concentration and self-confidence simultaneously contributed to upper serve accuracy in male volleyball players. These findings indicate that psychological aspects such as concentration and self-confidence play an important role in supporting athlete performance, particularly in fundamental skills like upper serve